arlige ord på fri fod. Åben debat og netværk på tværs af faglige og geografiske grænser er uomgængelige for at skaffe kvalificerede løsninger på den moderne idræts problemer. - Andersen, Jens Sejer (Forum for Idræt, 2008)
Artiklen omhandler sportsverdens problemer, at lukke op for kritik og debat. Jens Sejer Andersen: Dangerous words Due to lack of credible internal and external control mechanisms sport is vulnerable to organised crime and individual corruption. International sports organisations often react with threats and intimidation towards those who openly raise critical sports governance issues. The federations often settle in countries that are reluctant to monitor their business practices, and on the inside the sports organisations are marked by a family culture that seeks to suppress conflicts rather than debating and solving them in open democratic procedures. It is necessary to create networks across professional and geographical boundaries in order to help sport find solutions to its inherent governance problems.